Implementation the Knuth Morris Pratt (KMP) Algorithm in Interactive Web Monitoring and Recording Rabbit Reproduction System - Halimah Tus Sadiah; Muhamad Saad Nurul Ishlah (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2019)
Recording and monitoring rabbit reproduction data at Balai Penelitian Ternak (Balitnak) are yet integrated using systematic recording and searching system approach. Thus the purpose of this study is to build an interactive web monitoring and recording rabbit reproduction system as well as implementing the Knuth Morris Pratt (KMP) algorithm in order to provide a reliable search function. This research produced an interactive monitoring of recording rabbit reproduction data which record important information about rabbit codes, dates (mating, palpation, childbirth, 21 days, 35 days), weight (mating, palpation, after giving birth, 21 days, 35 days ), the number of children born alive or dead (giving birth, 21 days, 35 days). The results of the implementation of the KMP algorithm generated a search with a time of 0.015095 milliseconds with an algorithm test based on the search for rabbit names as many as 20 types of rabbits.